2015
DOI: 10.1007/s11626-015-9910-2
|View full text |Cite
|
Sign up to set email alerts
|

Novel model of innate immunity in corneal infection

Abstract: The cornea functions as the major refractive interface for vision and protects the internal eye from insult. Current understanding of innate immune responses to corneal infection derives from a synthesis of in vitro and in vivo analyses. However, monolayer cell cultures and mouse models do not accurately duplicate all aspects of innate immunity in human patients. Here, we describe a three-dimensional culture system that incorporates human cells and extracellular matrix to more completely simulate the human cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Prior studies demonstrated unequivocally the capacity of cultured keratocytes to express biologically significant quantities of CXCL8, prior to the expression of other chemokines tested (Natarajan et al 2003). We also showed in an in vitro 3-dimensional model of the human cornea that in the absence of any other cell type, the presence of keratocytes is sufficient for infiltration of peripheral blood leukocytes upon HAdV-D37 infection (Rajaiya et al 2015). We also demonstrated previously using CXCL1 −/− and CXCR2 −/− mice that deficiency of either CXCL1 or its receptor resulted in delayed infiltration of neutrophils, but not reduced numbers of inflammatory monocytes in HAdV-D37 corneal infection (Chintakuntlawar and Chodosh 2009).…”
mentioning
confidence: 90%
“…Prior studies demonstrated unequivocally the capacity of cultured keratocytes to express biologically significant quantities of CXCL8, prior to the expression of other chemokines tested (Natarajan et al 2003). We also showed in an in vitro 3-dimensional model of the human cornea that in the absence of any other cell type, the presence of keratocytes is sufficient for infiltration of peripheral blood leukocytes upon HAdV-D37 infection (Rajaiya et al 2015). We also demonstrated previously using CXCL1 −/− and CXCR2 −/− mice that deficiency of either CXCL1 or its receptor resulted in delayed infiltration of neutrophils, but not reduced numbers of inflammatory monocytes in HAdV-D37 corneal infection (Chintakuntlawar and Chodosh 2009).…”
mentioning
confidence: 90%
“…Corneal facsimiles, comprised of cornea cells grown in matrices, have sought to mimic the 3D structure of the cornea and cell-to-cell interactions in a renewable and cost-effective manner. One such model consists of human corneal stromal fibroblasts mixed with type I collagen in transwell plates overlaid with Matrigel to simulate the corneal stroma and basement membrane and this model has been used for corneal inflammation and adenovirus infection studies [ 91 ]. Subsequent improvements consisted of culturing epithelial cells over these stromal cells and the incorporation of an endothelium to create full thickness corneal equivalents [ 92 ].…”
Section: In Vitro 3d Cell Culture/explant Systemsmentioning
confidence: 99%
“…Matrigel is a gelatinous protein complex secreted by cultured mouse sarcoma cells, containing many components of epithelial basement membrane, and previously shown to bind interferon gamma . Immunohistochemistry performed on facsimiles overlaid with Matrigel and after overnight infection with HAdV‐D37 showed foci of CXCL8 bound to the Matrigel, and colocalized to heparan sulfate . Heparan sulfate is a component of corneal epithelial basement membrane also present in Matrigel, and expected to bind to CXCL8 because of its negative charge .…”
Section: Modeling Host Immune Responses In Ekcmentioning
confidence: 99%